2009
DOI: 10.4076/1757-1626-2-8334
|View full text |Cite
|
Sign up to set email alerts
|

Neurosyphilis presenting with dementia, chronic chorioretinitis and adverse reactions to treatment: a case report

Abstract: Neurosyphilis results from infection of the brain, meninges or spinal cord by Treponema pallidum and develops in about 25%-40% of persons who are not treated for syphilis. This article reports a rare case of active neurosyphilis with mild dementia, chronic chorioretinitis, and hearing loss. During the treatment with Penicillin, a rare combination of complications such as Jarisch-Herxheimer and Hoigné reactions were observed.The clinical feature is characterized by a slow progressive cognitive decline and behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 8 publications
1
14
0
2
Order By: Relevance
“…For instance, Fujimoto et al [6] reported a case who presented with immediate, recent and remote memory disturbances. This was consistent with previously reported cases [7,8,9,10,11]. Unfortunately, these studies lacked systematic neuropsychological examinations, and they did not include other dementia patient groups (e.g.…”
Section: Introductionsupporting
confidence: 91%
“…For instance, Fujimoto et al [6] reported a case who presented with immediate, recent and remote memory disturbances. This was consistent with previously reported cases [7,8,9,10,11]. Unfortunately, these studies lacked systematic neuropsychological examinations, and they did not include other dementia patient groups (e.g.…”
Section: Introductionsupporting
confidence: 91%
“…There are two forms of arteritis: Heubner arteritis, which is the more common form affecting the medium and large arteries, and Nissl-Alzheimer arteritis, which affects the small arteries and arterioles. Other manifestations of meningovascular syphilis include leptomeningeal and cerebral gummas [1,4-6]. …”
Section: Introductionmentioning
confidence: 99%
“…Seven were case reports [4][5][6][7][8][9][10], one was a cohort [1], and one was a case series [11]. Study characteristics are summarized in Table 1.…”
Section: Overviewmentioning
confidence: 99%